Annotated checklist of the grasshoppers and crickets (Orthoptera) of the Czech Republic - Holuša, Jaroslav; Kočárek, Petr; Vlk, Robert; Marhoul, Pavel (Zootaxa, 2013)
A checklist is presented of the Orthoptera of the Czech Republic. Based on the critical revision of published data and previous lists of species, which often contained only general or questionable data and which often inaccurately cited each other, we found 96 species of Orthoptera belonging to the fauna of the Czech Republic. We emphasize those changes that are based on comparison with previous checklists. We provide information on missing, unclear, and extinct species and on newly detected species, and we confirm the status of species that have been missing for a long time (Leptophyes boscii, Polysarcus denticauda, Ruspolia nitidula, Eumodicogryllus bordigalensis, Tetrix bolivari, Mecostethus parapleurus). We also note those species for which only several individuals have been detected (Pteronemobius heydenii) or those survived only at a single locality (Platycleis montana, Aiolopus thalassinus, Dociostaurus brevicollis, Omocestus petraeus) or at two localities (Poecilimon intermedius, Platycleis veyseli, Pseudopodisma nagyi). Phaneroptera nana is recorded as new for Bohemia.
Keywords: Grasshoppers; Animals; Česká republika; Checklist; kobylky; zvířata; Czech Republic; kontrolní seznam; Gryllidae